Specific Features of Counteracting VAT Evasion: Experience of Ukraine and Foreign Countries - N. S. Horobets (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on determining specific features of counteracting VAT evasion in Ukraine and foreign countries. It has been found out that the presence of VAT in the tax system of any state is a prerequisite for such a state to become a member of the European Union and it is due to its broad tax base and more neutral impact on economic decision-making on investment and consumption issues. It has been noted that the joint search by the states for the ways to combat VAT evasion is due to the need to minimize the damage caused to the financial and economic interests of the state by such actions, to increase the efficiency of value added tax, to increase the competitiveness level of domestic producers, to stimulate priority economic activities in the state. The content of value added tax as an indirect tax in accordance with the provisions of scientific doctrine has been revealed. Specific features of legal and illegal (tax crime) types of VAT evasion have been studied. The list of the methods to evade value added tax in Ukraine and foreign countries has been provided. The specifics of general and special ways to counteract this action have been revealed. The emphasis has been placed on such methods of counteracting VAT evasion as enshrining legal liability for VAT evasion at the legislative level; exercising tax control over the entities that are registered as value added taxpayers; usage of electronic document management and other opportunities of the digital economy, which allows to identify risks in the activities of taxpayers during their initial registration, etc. It has been concluded that there is no unified approach to the implementation of counteraction to value added tax evasion by state-authorized agencies; and the emphasis has been placed on the feasibility of existence of a basic list of the methods to counteract value added tax evasion.